Influence study of (Vitamin C) absorption on the mechanical properties of (Poly ethylene terphthalate) drinking bottles - Sameer Ahmed Awad (مجلة جامعة الانبار للعلوم الصرفة, 2012)
:In this research, the study shows the effect of vitamin C absorption by poly ethylene terphthalate (PET) bottles on mechanical properties of (PET) bottles that was investigated through tensile test. The polyethylene terphthalate bottle containing orange drinks with ( 50ppm ) initial concentration of vitamin C were stored for about three months at ( 10, 25 , 50 ºC ) and the mechanical properties ( tensile strength , modulus of elasticity and elongation ) of poly ethylene terphthalate bottles were measured periodly during the storage time . The effect of vitamin C on the mechanical properties of (PET ) bottles was compared between of the (PET ) bottles containing orange drinks with (50ppm ) vitamin C and the (PET ) bottles containing orange drink without concentration additional of vitamin C solution , maximum effect of vitamin C on mechanical properties of (PET) bottles was observed on the samples stored at 50ºC that could be represents to the high amount of absorbed vitamin C at high storage temperatures . It was also found that tensile strength and modulus of elasticity of ( PET ) bottles decreased with the absorption degree of vitamin C, while the elongation increased